2019
DOI: 10.1155/2019/7481341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Terminalia catappa Linn. on Biofilms of Candida albicans and Candida glabrata and on Changes in Color and Roughness of Acrylic Resin

Abstract: This study aimed to investigate the effect of the n-butanol fraction of Terminalia catappa Linn., (FBuTC) on biofilm of Candida albicans and Candida glabrata, as well as changes in color and roughness of polymethyl methacrylate resin (PMMA). The susceptibility of C. albicans and C. glabrata to FBuTC was evaluated by means of the Minimum Inhibitory and Minimum Fungicidal Concentration (MIC and MFC). PMMA acrylic resin discs (N= 108) were fabricated. For the susceptibility tests, biofilms of C. albicans and C. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…7,8 Secondary metabolites of the phenolic group are obtained from mangrove leaves with active compounds in the form of flavonoid and saponin, 9 rosella flower with active compounds in the form of anthocyanin, riboflavin, beta-carotene, polysaccharide, and flavonoid, 10 ketapang leaves with active compounds in the form of tannins and n-butanol (Terminalia catappa Linn). Fraction, 11 Mexican tea extract with the active compound form quercetin and kaempferol, grape seed extract with active compounds in the form of polyphenols. 12 The terpenoid compounds are lipophilic; the antifungal activity in the secondary metabolites of the terpenoid group can cause the membrane to be blocked from dissolving lipids found on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Secondary metabolites of the phenolic group are obtained from mangrove leaves with active compounds in the form of flavonoid and saponin, 9 rosella flower with active compounds in the form of anthocyanin, riboflavin, beta-carotene, polysaccharide, and flavonoid, 10 ketapang leaves with active compounds in the form of tannins and n-butanol (Terminalia catappa Linn). Fraction, 11 Mexican tea extract with the active compound form quercetin and kaempferol, grape seed extract with active compounds in the form of polyphenols. 12 The terpenoid compounds are lipophilic; the antifungal activity in the secondary metabolites of the terpenoid group can cause the membrane to be blocked from dissolving lipids found on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Neste sentido, pesquisas envolvendo compostos com propriedades antifúngicas de origem natural vêm aumentando (Gonçalves et al, 2019), inclusive na Odontologia. Desta forma, neste estudo, foi investigado e descrito pela primeira vez na literatura o efeito do extrato de A. chica em biofilmes de C. albicans sobre superfícies de resina acrílica, simulando a condição de biofilme na superfície de próteses dentais removíveis.…”
Section: Discussionunclassified
“…100 µL da solução stock do AchE foi transferida ao primeiro poço da placa de 96 poços e foi realizada a sua diluição seriada de forma a se obter o AchE nas concentrações 1,000 a 0.48 µg/ml. Nistatina (Sigma-Aldrich, St. Louis, MO, USA), Anfoterinina B (União Química Farmacêutica Nacional, SP, Brasil), e DMSO 2 % (veículo, v/v) (Gonçalves et al, 2019) foram utilizados como controles positivos e negativo, respectivamente. O meio de cultura estéril, o AchE, e a viabilidade do fungo também foram testadas.…”
Section: Determinação Da Concentração Inibitória Mínima E Fungicida Mínima (Cim/cbm)unclassified
“…Wight & Arn. ( Saivaraj and Chandramohan, 2018 ) and Terminalia catappa L. ( Gonçalves et al., 2019 ) bark, and Terminalia chebula Retz. fruit ( Vidya et al., 2019 ) extract demonstrated antifungal activity against the opportunistic yeasts including Candida albicans , C. glabrata , C. krusei , and C. tropicalis .…”
Section: Pharmacological Effects Of Active Constituents From mentioning
confidence: 99%
“…and Terminalia mantaly H. Perrier bark extracts inhibited Fusarium ssp., plant pathogenic fungi, with low MIC values ranging from 0.025–0.050 mg/mL ( Kouassi et al., 2019 ). Moreover, the leaf extract from Terminalia catappa L. exhibited antibiofilm activity against C. albicans and C. glabrata ( Gonçalves et al., 2019 ). The information indicated that the extracts of Terminalia sp.…”
Section: Pharmacological Effects Of Active Constituents From mentioning
confidence: 99%